Analisis Tahap Pelaksanaan Pembelajaran Berdiferensiasi pada Pembelajaran Bahasa Jawa Materi Geguritan di Kelas IV Sekolah Dasar - Ade Risma Syfa Zahra; Sri Marmoah; Joko Daryanto (Universitas Sebelas Maret, 2026)
This study aims to describe the implementation stage of differentiated learning in terms of content, process, product, and learning environment differentiation in Javanese language learning on Geguritan material in Grade IV of SD Negeri 2 Urutsewu. This study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation using purposive sampling. The results showed that differentiated learning was implemented through four elements. Content differentiation was implemented through diagnostic assessments and the adjustment of learning materials, resources, and media according to students’ needs. Process differentiation was applied through flexible grouping, varied learning activities, peer tutoring, individual feedback, and learning reflection. Product differentiation was implemented by providing choices of learning outcomes in the form of written geguritan, posters, and geguritan reading videos, while learning environment differentiation was realized through a safe, comfortable, and inclusive learning atmosphere that supports students’ diverse learning needs. Thus, differentiated learning is able to accommodate students’ diverse learning needs, making learning more active, meaningful, and student-centered.